Adding body load modifies the vibratory sensation of the foot sole and affects the postural control - Jammes, Yves (Mil Med Res, 2018)
BACKGROUND: Heavy backpacks are often used by soldiers and firefighters. Weight carrying could reduce the speed and efficiency in task completion by altering the foot sole sensitivity and postural control. METHODS: In fifteen healthy subjects, we measured the changes in sensitivity to vibrations applied to the foot sole when standing upright or walking after load carrying (30% body weight). The participants were asked to judge different vibration amplitudes applied on the 2nd or 5th metatarsal head and the heel at two frequencies (25 and 150 Hz) to determine the vibration threshold and the global perceptual representation (Ѱ)of the vibration amplitude (Ф) given by the Stevens power function (Ѱ = k × Ф(n)). Any increase in negative k value indicated a reduction in sensitivity to the lowest loads. Pedobarographic measurements, with computation of the center of pressure (COP) and its deviations, were performed during weight carrying. RESULTS: The 25-Hz vibration threshold significantly increased after weight carrying when standing upright or walking. After standing with the added loads, the absolute negative k value increased for the 25 Hz frequency. After walking with the added loads, the k coefficient increased for the two vibration frequencies. Weight carrying significantly increased both the CoP surface and CoP lateral deviation. CONCLUSIONS: Our data show that weight carrying reduces the sensory pathways from the foot sole and accentuates the center of pressure deviations.